2015
DOI: 10.1007/s40140-015-0098-5
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Focused Cardiac Ultrasound (FoCUS) in Obstetrics

Abstract: Focused cardiac ultrasound (FoCUS) is emerging as a safe, convenient, and cost-effective method to non-invasively assess complex hemodynamics. This technique has particular promise in the obstetric population, with important applications such as assessment of preload and contractility, in a range of clinical circumstances. Although outcome data remain sparse, anesthesiologists should consider incorporating FoCUS into the management of obstetric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Performing serial FOCUS can be an adequate replacement for serial standard echocardiography by a cardiologist. It is financially beneficial for both the patient and the health system, and provides similar information regarding function of the left ventricle, identifying pericardial effusion, and assessing intravascular volume for the physicians [4,11]. A study by Mandavia et al showed 96% sensitivity and 98% specificity for FOCUS in identifying pericardial effusion [12].…”
Section: Discussionmentioning
confidence: 99%
“…Performing serial FOCUS can be an adequate replacement for serial standard echocardiography by a cardiologist. It is financially beneficial for both the patient and the health system, and provides similar information regarding function of the left ventricle, identifying pericardial effusion, and assessing intravascular volume for the physicians [4,11]. A study by Mandavia et al showed 96% sensitivity and 98% specificity for FOCUS in identifying pericardial effusion [12].…”
Section: Discussionmentioning
confidence: 99%